Case Report: Arterial Thrombosis in a Dalmatian dog - Guevara-Ortiz, Pablo Francisco; Rubio-Arias, Pablo Giovanny; Zúñiga-Velarde, José Julián; Fernández-Jara, Adriana Estefanía (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
Arterial thrombosis included as a differential diagnosis in acute claudication in dogs is rare. Most common causes are usually trauma, neoplasia or osteo degenerative diseases. The clinical case of a 6.5-year-old Dalmatian male dog with a history of sudden claudication of the left thoracic limb, weakness and respiratory distress is described. The elevated values of D-Dimer and C-Reactive Protein, and Ultrasound study confirmed the presence of a thrombus in the radial brachial artery. The cause for the thrombus was not identified. Medical management included Enoxaparin, and long-term medication with Clopidogrel, Rivaroxaban, and Atenolol.